Clemente Romano, sembrador de fraternidad en la Carta a los Corintios = Clement of Rome, planter fraternity in the Letter to the Corinthians - Castellaro, María Inés (Veritas, 2016)
Clement of Rome is the man of reconciliation, which seeks to sow those who hear a seed of fraternity. He knows the heart of man nest evil passions, feelings of envy and division but also knows that whoever lives in love, who sets her sights on the God who is Love becomes becomes. The only way is Jesus Christ and so continuously invited, through his words, to stare at him. Mercy, humility, simplicity, fraternal correction, hospitality are words along the Corinthians intertwine weaving Brother love story and love of God. What can we learn this letter written many centuries ago and it seems so today? It is a challenge for pilgrims today man who feels the one hand, the thirst for spirituality, and secondly, the lust of power, possessions, pleasure, to contemplate a God who loves him and seek only good brother walking beside him with simplicity and humility.